MANAJEMEN PEMERINTAHAN DALAM PENGELOLAAN PENGADUAN MASYARAKAT MELALUI APLIKASI PEKAN KITA (PEKA) DI KOTA PEKANBARU TAHUN 2023-2024 - Rifda, Melani Adelia; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the many problems in the PEKA application which is a means of public complaints to the government regarding public services that can be handled immediately, the purpose of creating the PEKA application is to integrate with OPDs in Pekanbaru, but in its implementation not all OPDs are registered in the application. In addition, there are several other problems in terms of security, and lack of socialization. The public complaint mechanism in PEKA application includes submitting complaints, receiving or recording, distributing, examining, resolving or following up, and reporting. The purpose of this study is to see whether government management in managing public complaints through PEKA application has been running well or not by looking at the management mechanism for both the application and complaint management. The research method used in this study is a qualitative approach and descriptive research type. Data collection techniques are carried out by interviews and documentation. This study uses the Government Management Theory according to G.R.Terry with indicators of planning, organizing, implementing, and supervising. The results of the study found that government management in managing public complaints through PEKA application in Pekanbaru City in 2023-2024 has not been implemented optimally, because there are several aspects that have not been running well, namely the aspects of organizing and implementing. comprehensive and massive socialization has not been carried out either to fellow OPDs or the community, so that only 4 OPDs are registered in the application, and many people do not know about this application. In terms of implementation, it has not been running optimally, where this implementation is seen from the process of following up on public complaints, of the 15 complaints received in 2023-2024, not all of them were processed to completion. In addition, this application cannot be reused due to waiting for the recovery queue after being affected by the PDN hack in mid-2024. Keywords: Government Management, Application, Complaints